2022
DOI: 10.3390/cancers14235962
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Destabilizer Eribulin Synergizes with STING Agonists to Promote Antitumor Efficacy in Triple-Negative Breast Cancer Models

Abstract: Eribulin is a microtubule destabilizer used in the treatment of triple-negative breast cancer (TNBC). Eribulin and other microtubule targeted drugs, such as the taxanes, have shared antimitotic effects, but differ in their mechanism of microtubule disruption, leading to diverse effects on cellular signaling and trafficking. Herein, we demonstrate that eribulin is unique from paclitaxel in its ability to enhance expression of the immunogenic cytokine interferon beta (IFNβ) in combination with STING agonists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The mechanistic basis for this synergy involves the cGAS protein's affinity for DNA termini, thereby impeding the access of critical DNA repair machinery components, including the MRN complex (comprising MRE11, RAD50, and NBS1) and 53BP1—both vital for the initial phases of DNA repair processes like homologous recombination (HR) and non-homologous end joining (NHEJ) 18 . Consistent with prior findings, our data indicate that ERI preferentially activates the cGAS-STING pathway compared to PTX, reinforcing the notion that a combined ERI and STING agonist therapy could be a viable oncological strategy 36 , 37 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mechanistic basis for this synergy involves the cGAS protein's affinity for DNA termini, thereby impeding the access of critical DNA repair machinery components, including the MRN complex (comprising MRE11, RAD50, and NBS1) and 53BP1—both vital for the initial phases of DNA repair processes like homologous recombination (HR) and non-homologous end joining (NHEJ) 18 . Consistent with prior findings, our data indicate that ERI preferentially activates the cGAS-STING pathway compared to PTX, reinforcing the notion that a combined ERI and STING agonist therapy could be a viable oncological strategy 36 , 37 .…”
Section: Discussionsupporting
confidence: 90%
“…In vivo studies have demonstrated the potential therapeutic efficacy of combining ERI with STING agonists 36 . The mechanistic basis for this synergy involves the cGAS protein's affinity for DNA termini, thereby impeding the access of critical DNA repair machinery components, including the MRN complex (comprising MRE11, RAD50, and NBS1) and 53BP1—both vital for the initial phases of DNA repair processes like homologous recombination (HR) and non-homologous end joining (NHEJ) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the STING pathway is activated by mitochondrial or nuclear DNA release induced by cellular damage resulting from the treatment with MTAs, but it has also been proposed that STING activation occurs downstream of the microtubule disruption triggered by these chemotherapeutics. 12 , 54 , 72 Whatever the precise mechanism turns out to be, the discovery that vinorelbine-induced pain depends on STING-type I IFN signaling makes it possible to implement strategies to alleviate the neuropathic pain state caused by the chemotherapeutic. We demonstrate that this can be achieved by targeting MNK1-eIF4E signaling.…”
Section: Discussionmentioning
confidence: 99%
“…STING1, an ER-bound protein, is crucial for autophagy and programmed cell death (Zhang et al, 2021a). A recent study shows that Eribulin, an anti-cancer drug used to treat breast cancer and liposarcoma, triggers cancer cell death via the STING1-dependent signaling axis (Fermaintt et al, 2021;Takahashi-Ruiz et al, 2022), indicating its role as a cell-death-promoting factor. Upregulation of these proapoptotic proteins may be induced in response to HLCS suppression.…”
Section: Discussionmentioning
confidence: 99%